Status Unsur Hara N, P dan K Tanah Inseptisol pada Tiga Penggunaan Lahan di Desa Semadin Lengkong Kecamatan Nanga Pinoh Kabupaten Melawi - Dewanti, Aplince Della; Krisnohadi, Ari; Nuriman, Muhammad (Fakultas Pertanian Universitas Tanjungpura, 2024)
This study aims to determine the nutrient status of N, P and K on three land uses and provide fertilization advice on each land use. This research was conducted in Semadin Lengkong Village, Nanga Pinoh sub-district, Melawi Regency. Soil samples for each research location were taken at 5 observation points of each land with a depth of 0-30 cm. The total number of samples on three land uses (oil palm, rubber and field rice) were 3 whole samples and 3 composite samples. Data analysis using descriptive analysis based on the criteria table of the Soil Research Center, 1983. Parameters of soil physical properties include soil color, soil drainage, soil texture, soil structure and soil content weight. The parameters of soil chemical properties include soil pH, soil total nitrogen, soil total phosphorus, soil total potassium, organic carbon as well as Al-dd content and soil Al saturation. The results showed that the soil N-total content in the three land uses entered into moderate criteria, the soil P-total content in the three land uses entered into very low criteria and the soil K-total content in oil palm land entered into very low criteria while in rubber land and paddy fields entered into low criteria. The high and low status of N, P and K nutrients is influenced by pH, organic carbon, and Al saturation. Soil reaction (pH) is included in the acid criteria, Carbon (C-Organic) is moderate, Al-dd content and soil Al saturation fall into high criteria. Furthermore, the recommended dose of fertilization on each land use is as follows, on oil palm land: Urea as much as 2.5kg/tree, SP-36 as much as 2kg/tree and KCL as much as 3.66 kg/tree. Rubber land: Urea as much as 287g/tree, SP-36 as much as 137 g/tree and KCL as much as 1,357g/tree. Paddy field: Urea as much as 223.66kg/ha, SP-36 as much as 55.55kg/ha, and KCL as much as 4,433.48kg/ha.